BILATERAL SIMULTANEOUS RHEGMATOGENOUS RETINAL DETACHMENT: Clinical Characteristics and Surgical Outcome. Issue 8 (August 2019) - Singh, Niharika; Jain, Mukesh; Jaisankar, Durgasri; Sharma, Tarun; Raman, Rajiv
Abstract : Purpose: To elucidate the clinical characteristics and surgical outcome of consecutive patients with bilateral simultaneous retinal detachment who reported to a tertiary eye care institution over a period of 10 years. Methods: Retrospective interventional consecutive study of 168 eyes of 84 patients with bilateral simultaneous retinal detachment, observed by indirect ophthalmoscopy at the initial examination was performed. Demographic and clinical characteristics were collected before and after surgery. Patients with attached retina at final follow-up were considered to have anatomical success and those with two or more lines improvement in visual acuity were considered to have functional success. Results: Most cases (90% in the better eye and 82.1% in the worse eye) were managed by scleral buckling procedure. With scleral buckle, anatomical success was seen in 99% and functional success was seen in 87% of the cases. Pars plana vitrectomy was performed in remaining cases with anatomical success in 83% and functional success in 78% of cases. Eyes with partial retinal detachment, without macular involvement, and eyes in which additional surgeries were not performed had significantly better anatomical and functional results. Conclusion: Early sequential surgery gives good anatomical and functional outcomes. Surgical outcomes were better with scleral buckling than pars plana vitrectomy. Abstract : A retrospective analysis of 168 eyes of 84 patients with bilateral retinal detachment was performed. We described the clinical characteristics of bilateral retinal detachment and comparison of surgical outcomes in each characteristics.